Durability of concrete produced with proven internal curing agents subjected to the action of chloride - Giordani Berton, Julia; Pinto da Silva Filho, Luiz Carlos (Revista ALCONPAT, 2023)
The procedure to promote internal curing is one of the strategies to reduce the shrinkage process of high strength concrete with low water/cement ratio. Various materials have been used as curing agents, such as porous materials, which must meet the minimum requirements defined by ASTM C1761. This research sought to contribute to the development of new ways to inhibit the degradation of reinforced concrete structures through the use of ceramic shell and expanded clay, used as an internal curing agent in concrete subjected to the action of chlorides. Based on the results found, it is possible to verify that the selected aggregates, mainly the ceramic shell, contributed to the improvement of the mechanical properties and durability of the concretes in the evaluated conditions.